2023
DOI: 10.3390/su15086827
|View full text |Cite
|
Sign up to set email alerts
|

The Embedded Agroecology of Coffee Agroforestry: A Contextualized Review of Smallholder Farmers’ Adoption and Resistance

Abstract: Contemporary ecology and agronomy point to the many benefits of agroforestry crop systems for the provision of ecosystem services by regenerating native ecologies, and in many contexts, socio-economic benefits for coffee farmers, especially the contribution of nitrogen-fixing trees’ litter to soil nutrition and water retention. However, the implementation of agroforestry in coffee cultivation is thus far incomplete and uptake has been uneven. In this paper, we examine the adoption and non-adoption of agrofores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…This study's outcome also agreed with several other research outputs [ 2 , 4 , 5 , 32 , 34 , [44] , [45] , [46] , [47] , [48] , [49] ] who generally and concisely reported that taller plant heights were observed when grown using organic amendments such as forest soil, decomposed coffee husk, farmyard manure, vermicompost, animal and plant biochar etc. This could be because of a huge amount of organic matter and total nitrogen present [ 15 , 17 , 19 , 50 ] which enhance the capacity to easily uptake nutrients [ 42 , 51 ], maintain soil moisture and enhance soil fertility [ 52 , 53 ] that ultimately improves growth media porosity, aeration and water retention capacity [ 54 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This study's outcome also agreed with several other research outputs [ 2 , 4 , 5 , 32 , 34 , [44] , [45] , [46] , [47] , [48] , [49] ] who generally and concisely reported that taller plant heights were observed when grown using organic amendments such as forest soil, decomposed coffee husk, farmyard manure, vermicompost, animal and plant biochar etc. This could be because of a huge amount of organic matter and total nitrogen present [ 15 , 17 , 19 , 50 ] which enhance the capacity to easily uptake nutrients [ 42 , 51 ], maintain soil moisture and enhance soil fertility [ 52 , 53 ] that ultimately improves growth media porosity, aeration and water retention capacity [ 54 ].…”
Section: Resultssupporting
confidence: 89%
“…Coffee is cultivated in more than 60 countries located in tropical and subtropical regions of the world [ 1 ]. Its agro-ecosystems support millions of farmers through income-generating and offering environmental services [ [2] , [3] , [4] , [5] , [6] ]. Coffee is one of the main crops grown in countries such as Brazil, Vietnam, Colombia, Indonesia, and Ethiopia [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The coffee sector is facing challenges, including climate change [9][10][11][12][13], which has been well-documented [9,14,15]. Farming systems are already transitioning towards agroforestry [16][17][18][19], but a significant part of the solution will undoubtedly be genetic [20][21][22]. Coffea arabica is one of the most genetically narrow cultivated species [23,24], primarily due to drastic bottlenecks during its evolution [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Coffee is a product that is in much demand in different countries and is the most consumed beverage, surpassing tea and other popular drinks like beer (Olajire 2020). Coffee cultivation has evolved, embracing a wide range of species of forests (Wienhold and Goulao 2023), vegetables (Osorio-Velásquez and Pombo 2019), and animals (De Leijster et al 2021). Moreover, coffee plantations with agroforestry systems have become more prevalent and representative of the industry (Wienhold and Goulao 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Coffee cultivation has evolved, embracing a wide range of species of forests (Wienhold and Goulao 2023), vegetables (Osorio-Velásquez and Pombo 2019), and animals (De Leijster et al 2021). Moreover, coffee plantations with agroforestry systems have become more prevalent and representative of the industry (Wienhold and Goulao 2023). This approach fosters a symbiotic relationship between coffee crops and surrounding vegetation, enhancing sustainability and ecological bene ts (Siles et al 2022).…”
Section: Introductionmentioning
confidence: 99%